Bangladesh : Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2003)
The paper presents statistical data on gross domestic product, agricultural production, manufacturing production, energy statistics, retail prices of petroleum products, consumer price index, central government operations, revenues, and central expenditure in Bangladesh. It also presents the central government food account, consolidated accounts and profits of nonfinancial public enterprises, government domestic securities, monetary survey, balance sheet of the monetary authorities, interest rate structure of the banking, exports, geographical distribution of foreign trade, external aid, external debt, summary of the tax system, and other related economic indices.